Digital analysis of tooth microwear, a potential application for dental microwear monitor. Issue 1 (4th January 2022) - Xue, Gang; Hu, Conghu; Du, Jianke; Hua, Licheng
Abstract: In general, tooth wear is difficult to be noticed until it leads to toothache in vivo. Developing a dynamic dental wear monitoring system to predict tooth wear in daily life is a necessity. The translation between complex surface wear morphology and corresponding digital signal source is a technical limitation to develop this kind of monitoring system. Microwear texture analysis has been widely employed in predicting diet by a palaeontologist. The main question is whether the microwear texture analysis has potential development space to develop a sensor for monitoring tooth wear. According to obtained results, the microwear texture analysis had enough sensitivity to display the surface morphology variations for different chewing foods and various angles. The corresponding sensitive digital signal of tooth microwear surface morphology makes it possible to develop a dental microwear sensor.